Biomaterials to model and measure epithelial cancers. (November 2018) - Beri, Pranjali; Matte, Bibiana; Fattet, Laurent; Kim, Daehwan; Yang, Jing; Engler, Adam
Abstract The use of biomaterials has substantially contributed to both our understanding of tumorigenesis and our ability to identify and capture tumour cells in vitro and in vivo. Natural and synthetic biomaterials can be applied as models to recapitulate key features of the tumour microenvironment in vitro, including architectural, mechanical and biological functions. Engineered biomaterials can further mimic the spatial and temporal properties of the surrounding tumour niche to investigate the specific effects of the environment on disease progression, offering an alternative to animal models for the testing of cancer cell behaviour. Biomaterials can also be used to capture and detect cancer cells in vitro and in vivo to monitor tumour progression. In this Review, we discuss the natural and synthetic biomaterials that can be used to recreate specific features of tumour microenvironments. We examine how biomaterials can be applied to capture circulating tumour cells in blood samples for the early detection of metastasis. We highlight biomaterial-based strategies to investigate local regions adjacent to the tumour and survey potential applications of biomaterial-based devices for diagnosis and prognosis, such as the detection of cellular deformability and the non-invasive surveillance of tumour-adjacent stroma. This Review discusses how biomaterials can be used to recreate and understand the influence of specific tumour microenvironment properties on cancer progression and highlights materials-based strategies to capture, detect and assess metastatic cancer cells in vitro and in vivo.